Analisis Kontribusi Pajak Penunjang Sektor Pariwisata Di Kota Banjarmasin - Addiina, Fahma; Rizali (PPJP ULM, 2024)
This study examines the contribution and the impact of restaurant, hotel, entertainment, and parking taxes on Banjarmasin's local tax revenue and income, using quantitative descriptive methods and double linear regression analysis. According to the study's findings, the local tax contribution from restaurants falls into the middle range, that from hotels falls into the lower range, and that from entertainment and parking taxes. Restaurant taxes make up a smaller portion of local government revenue than hotels, entertainment taxes, and parking fees. While restaurant, entertainment, and parking taxes partially have no major influence, hotel taxes have a significant impact. 81% of the local government revenue in the Banjarmasin city area is influenced by the combined effects of the restaurant tax, hotel tax, entertainment tax, and parking tax. The remaining 19% is influenced by other factors.